Bmal1 deficiency in neutrophils alleviates symptoms induced by high-fat diet - Brinja Leinweber; Violetta Pilorz; Iwona Olejniczak; Ludmila Skrum; Kimberly Begemann; Isabel Heyde; Sarah Stenger; Christian David Sadik; Henrik Oster (iScience)
Summary: Physiological processes, including metabolism and immune responses, are generated by the circadian clock, driven by clock genes. Disrupting circadian rhythms through a high-fat diet promotes obesity and inflammation. Studies show that deleting the clock gene, brain, and muscle ARNT-like 1 (Bmal1) in adipose tissue leads to overeating and weight gain. We now show that Bmal1 deletion in neutrophils protects against diet-induced obesity and reduces inflammatory macrophage infiltration into epididymal white adipose tissue (eWAT), despite increased food intake over 20 weeks of a high-fat diet. This protection is linked to enhanced energy expenditure, increased UCP1 expression in iBAT, improved insulin sensitivity, and altered expression of genes encoding chemokine receptors CXCR2, CXCR4, and the ligand Cxcl2 in eWAT. Our findings reveal a key role of Bmal1 in neutrophils in regulating high-fat diet-induced adipose inflammation and emphasize circadian regulation’s importance in immuno-metabolic function.